Perceived social support and global self-worth in adolescents - Chua, Yee Chii; Chua, Bee Seok; Agnis Sombuling, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aims to determine whether adolescents’ global self-worth can be predicted through perceived social support from the parents, peers, and teachers. A self-report survey was administrated to a group of adolescents (N=100) with age ranging from 13 to 18 years; selected using the purposive sampling technique. Two scales were used for data collection: the Social Support Scale for Children and Adolescent (SSSCA) and Self-Perception Profile for Adolescents (SPPA), developed by Harter (2012). Multiple Regressions predicting adolescents’ global self-worth from perceived social support (parents, peers and teachers) were conducted. The results indicated that the combination of perceived social support significantly predicted the adolescents’ global self-worth, F (3, 96) = 5.97, p < 0.01. Surprisingly, the finding revealed that increased social support from peers predicted improved global self-worth, (β = .322, p < 0.01), whilst there was no significant contribution from the parents and teachers support towards global self-worth among adolescents. Results are discussed with respect to potential mechanisms through which social support and global self-worth may operate. The implications of the study and recommendation for future research are presented.